Dehalogenation produces graphene wrapped carbon cages as fast-kinetics and large-capacity anode for lithium-ion capacitors. (15th January 2023) - Ma, Yibo; Wang, Kai; Xu, Yanan; Zhang, Xudong; Peng, Qifan; Li, Shani; Zhang, Xiong; Sun, Xianzhong; Ma, Yanwei
Abstract: The sluggish kinetics of battery-type anode limits the realization of high capacitance especially at elevated charge-discharge rates for lithium-ion capacitors (LICs). In this work, graphene wrapped carbon cages (Gx Py ) are obtained via a facile physical-confined pyrolysis approach from graphene oxide (GO)/polyvinylidene fluoride (PVDF), which exhibits great promise as a fast and large-capacity anode for LICs. The thermal degradation process analysis reveals that carbon cages with abundant mesopores derived from the dehalogenation of PVDF are formed spontaneously due to the HF releasing in the pyrolysis process with the aid of physical confined GO template. Hollow carbon cages could ameliorate the Li + transport path, while 2D graphene serves as a conducting bridge connecting the isolated carbon cages to minimize the barrier of charge transfer. As a result, a LIC pouch-cell based on Gx Py hierarchical carbon anode demonstrates high energy density and superior power density, as well as remarkable cycle life. This study may open a unique avenue for designing fast and large-capacity carbon anode and push the development of high-performance LICs. Graphical abstract: We report a physical-confined pyrolysis pathway to prepare hierarchical carbon anode composed of graphene wrapped carbon cages. Carbon cage structure can ameliorate the Li + transport path, while graphene serves as a conducting bridge connecting the isolated carbon cages, resulting fast kinetics and large capacity as anode material. As a result, a LIC pouch-cell based on Gx Py hierarchical carbon anode demonstrates impressive electrochemical performance. Image 1 Highlights: A physical-confined pyrolysis pathway is developed to prepare hierarchical carbon anode composed of graphene wrapped carbon cages. The thermal degradation mechanism reveals that carbon cages are derived from the dehalogenation of PVDF due to the HF releasing in the pyrolysis process. Cage structure can ameliorate Li + transport path, resulting fast kinetics and large capacity as anode material.